Powered by www.myengg.

com

SUCCESSIVE – DIFFERENTIAL
PREVIOUS EAMCET BITS 1.
y = ea sin
−1

x

⇒ (1 − x 2 ) y n + 2 − ( 2n + 1) xy n +1 =

[EAMCET 2009]

1) ( n 2 + n 2 ) y n

2) ( n 2 − a 2 ) y n
a 1− x2

3) ( n 2 + a 2 ) y n

4) − ( n 2 − a 2 ) y n

Ans: 3 Sol: y = ea sin x , ⇒ y1 = y x
2 ⇒ (1 − x 2 ) y1 = a 2 y 2
−1

2 ⇒ 2 (1 − x 2 ) y1 y 2 − 2xy1 = 2a 2 yy1

(1 − x ) y
2

2

− xy1 = a 2 y ………….(1)

Diff. (1) ‘n’ times using Leibnitz theorem (1 − x 2 ) y n + 2 − ( 2n + 1) xy n +1 = ( n 2 + a 2 ) y n 2. If y = sin ( log c x ) then x 2

d2 y dy +x = 2 dx dx 3) y 2 4) − y

[EAMCET 2008]

1) sin ( log e x ) Ans: 4 Sol: y = sin ( log x ) ⇒
⇒x

2) cos ( log e x )

dy 1 dy = cos ( log x ) ⇒ x = cos ( log x ) dx x dx

d 2 y dy 1 + = − sin ( log x ) 2 dx dx x d2 y dy +x = −y 2 dx dx d2 y dy −x = 2 dx dx 3) 25 y 4) –25 y

⇒ x2 3.

x = cos θ, y = sin 5θ ⇒ (1 − x 2 ) 1) −5y Ans: 4 2) 5y

[EAMCET 2007]

Sol:

dy −5cos 5θ −5 1 − sin 2 5θ = = dx sin θ 1 − cos 2 θ

1 − y2 = −5 = y1 1− x2

(1 − x ) y
2

2 1

= 25 (1 − y 2 ) ⇒ (1 − x 2 ) y 2 − xy1 = −25y
49

Powered by www.myengg.com

Powered by www.myengg.com

Successive – Differential

4.

f ( x ) = e x sin x ⇒ f ( 1) e6x sin 6x Ans: 2

6)

(x) =
3) 8e x sin x

[EAMCET 2006]
4) 8e x cos x

2) −8e x cos x

Sol: f ( x ) = eax sin bx f n ( x ) = ( a 2 + b2 )
n/2

.eax sin ( bx + n tan −1 b / a )

a = 1, b = 1, n = 6
f 6 (x) =

(

(1 + 1) )

6

e x sin ( x + 6 tan −1 (1) )

⎛ 3π ⎞ = 8e x sin ⎜ + x ⎟ = −8e x cos x ⎝ 2 ⎠
5. y = sin −1 x ⇒ (1 − x 2 ) d2 y = dx 2

[EAMCET 2004]

dy 1) − x dx
Ans: 3 Sol: y = sin −1 x ⇒ y1 =
2 ⇒ (1 − x 2 ) y1 = 1

2) 0

dy 3) x dx

⎛ dy ⎞ 4) x ⎜ ⎟ ⎝ dx ⎠

2

1 1− x2

2 ⇒ (1 − x 2 ) 2y1 y 2 − 2xy1 = 0

∴ (1 − x 2 ) y 2 = xy1 6. If I n = 1) n Ans: 4 Sol: I n = dn ( x n log x ) dx n dn ( x n log x ) , then In − nIn −1 = .... dx n 2) n – 1 3) n! 4) (n –1)!
[EAMCET 2003]

⎛1⎞ y = x n log x ⇒ y1 = x n ⎜ ⎟ + nx n −1 log x ⎝x⎠

( y1 )n −1 = nIn −1 + ( n − 1)!
⇒ I n − nI n −1 = ( n − 1) !

7.

If y = ae x + be− x + c , where a, b, c are parameters, then y′′′ = 1) y 2) y′ 3) 0 4) y′′

[EAMCET 2002]

Powered by www.myengg.com

Powered by www.myengg.com

Successive – Differential

Ans: 2 Sol. y = ae x + be − x + c y′ = ae x − be − x ; y′′ = ae x + be − x
y′′′ = ae x − be − x

y′′′ = y′
8. If y = a cos ( log x ) + b sin ( log x ) , where a, b are parameters, then x 2 y′′ + xy′ = [EAMCET 2002] 1) y Ans: 2 Sol: y = a cos ( log x ) + b sin ( log x )
xy′ = −a sin ( log x ) + b cos ( log x )

2) – y

3) 2y

4) –2y

xy′′ + y′ =

−aco s ( log x ) − b sin ( log x ) x

⇒ x 2 y′′ + xy′ = − y 9. If yk is the kth derivative of y with respect to x, y = cos(sinx) then y1 sin x + y 2 cos x = [EAMCET 2001]

1) y sin 3 x Ans: 4 Sol: Given y = cos(sinx)

2) − y sin 3 x

3) y cos3 x

4) − y cos3 x

⇒ y1 = − sin ( sin x ) .cos x y 2 = sin ( sin x ) .sin x − cos 2 x.cos ( sin x )

∴ y1 sin x + y 2 cos x = − sin ( sin x ) .sin x cos x + sin ( sin x ) sin x.cos x − cos3 x.cos ( sin x ) = − y cos3 x 10. dn x ( e sin x ) = dx n 1) 2n / 2.e x cos ( x + nπ / 4 ) 3) 2n / 2.e x sin ( x + nπ / 4 ) Ans: 3 Sol: y = eax sin ( bx ) ⇒ y n = where a = 1, b = 1 2) 2n / 2.e x cos ( x − nπ / 4 ) 4) 2n / 2.e x sin ( x − nπ / 4 )

[EAMCET 2000]

(

a 2 + b2

) .e
n

ax

b⎞ ⎛ sin ⎜ bx + n tan −1 ⎟ a⎠ ⎝

Powered by www.myengg.com

Powered by www.myengg.com

Successive – Differential

nπ ⎞ ⎛ y = e x sin x ⇒ y n = 2n / 2 e x sin ⎜ x + ⎟ 4 ⎠ ⎝

Powered by www.myengg.com